Slums, space and spirituality: religious diversity in contemporary Brazil. Issue 1 (18th October 2012) - Garmany, Jeff
<x xml:space="preserve">Abstract</x> Since the late 1980s, a growing body of academic literature has focused upon the 'evangelicalisation' of Latin America and other, less affluent world regions (e.g. Africa and Southeast Asia). Valuable for exploring a host of interconnected social, political, economic and cultural practices, this research has consistently pondered the implications of changing religious affiliations and what the effects of these changes might hold for society and space more generally. In Brazil, for example – with more Catholics than any country in the world and a rapidly growing evangelical population – researchers suggest that the country's spiritual shift may bring with it significant political and cultural change, particularly in the impoverished urban communities (i.e. favelas) where evangelical churches are most prominent. While numerous accounts exist to document these changes and reflect upon their potentialities, few geographers, as of yet, have contributed to these debates. Still unknown are the spatial changes that accompany this spiritual shift, the ways that neighbourhoods and cities are changing, and the day‐to‐day effects of new and syncretistic religious practices. Through a case study of a favela community in northeastern Brazil, this paper considers the socio‐spatialities of religious diversity and change within Brazil's contemporary urban landscape.